UPAYA NINIAK MAMAK DALAM MELESTARIKAN TRADISI BAARAK PADI KE MASJID SEBAGAI IDENTITAS LOKAL DI NAGARI PADANG LAWEH KECAMATAN KOTO VII KABUPATEN SIJUNJUJNG - Irsa Nurfa Inda Gustia; Azwar; Jamurin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Baarak Padi ke Masjid tradition is a cultural heritage of the people of Padang Laweh Village, Koto VII District, Sijunjung Regency, which is carried out after the rice harvest as an expression of gratitude to Allah SWT and serves as a symbol of local identity. The rapid development of modernization and external cultural influences has reduced the participation of the younger generation in preserving this tradition, making the role of niniak mamak (traditional leaders) increasingly important. This study aims to analyze the efforts of niniak mamak in preserving the Baarak Padi ke Masjid tradition as a local identity. This research employed a qualitative descriptive approach. Informants were selected using purposive sampling and consisted of the village head, niniak mamak, bundo kanduang, youth leaders, and community members. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model supported by Talcott Parsons' Structural Functionalism (AGIL) theory. The findings reveal that the tradition remains a local identity by promoting religious values, mutual cooperation, deliberation, and social solidarity. Preservation efforts include cultural value transmission, youth empowerment, collaboration with local government and community leaders, and the continuous implementation of the tradition.